Treatment-Related Complications and Functional Results after Ruthenium-106 Brachytherapy in Small to Medium Size Uveal Melanomas (Part 2) - Lalos, Fotios; Flühs, Dirk; Guberina, Maja; Bornfeld, Norbert; Stuschke, Martin; Sauerwein, Wolfgang; Bechrakis, Nikolaos E. (Klinische Monatsblätter für Augenheilkunde, 2024)
Purpose To analyze the treatment-related complications after ruthenium-106 brachytherapy in patients with uveal melanoma in terms of radiation-induced optic neuropathy, maculopathy and retinopathy, radiation-related vitreous hemorrhage, and retinal detachment, as well as secondary glaucoma and radiogenic cataract. In addition, the course of visual acuity was analyzed.Patients/Methods and Materials This retrospective study included 608 patients treated with ruthenium-106 brachytherapy between January 2008 and December 2010 at the Department of Ophthalmology, University Hospital Essen. The follow-up time was 11 years. The occurrence of the radiation-induced complications was analyzed using the Kaplan-Meier method. Cox regression was used for univariate and multivariate risk factor analyses. Hazard ratios were calculated for each variable.Results Regarding the complications, 34% (N = 207) of the patients had no reported side effects or complications during follow-up. Radiation optic neuropathy was observed in 18.8% (N = 114) of the patients, with a median time to onset of 16 months (range: 3 – 78 months). Radiation maculopathy occurred in 8.2% (N = 50) after a median time of 17 months (range: 3 – 67 months). Radiation retinopathy was observed in 20.1% (N = 122), with a median time to onset of 21 months (range: 6 – 67 months). Secondary glaucoma developed in 9.7% of the patients (N = 53) and radiogenic cataract in 46.8% (N = 227). Vitreous hemorrhage (11.8%, N = 72) and scleral necrosis (2.1%, N = 13) occurred relatively rarely.Conclusion The observed radiogenic complication rate is comparable with that reported in previous studies.
Keywords: uveal melanoma; 106-ruthenium; brachytherapy; epidemiology; choroid; retina; ocular tumors